2019
DOI: 10.1080/02640414.2019.1689807
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality to assess and train team ball sports performance: A scoping review

Abstract: Virtual reality (VR) is a widespread technology drawing an increasing interest for players and coaches, especially in team ball sports as it offers a simple tool to simulate, analyse and train situations that are often too complex to reproduce in the field. In this review we aimed at (1) providing an overview of methodologies and outcomes of research studies using VR in team ball sports; (2) better evaluating the potential interest of VR to analyse or train team ball sports situation and (3) identifying limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 92 publications
0
35
1
Order By: Relevance
“…Many ball sports in VR examined interception of balls, such as anticipating landing points and analyzing the influence of ball spins. However, only a few studies investigated throwing in VR so far (for review see [37]). [40] found that learning free throws in a CAVE is best when beginners see their performance from third-person perspective and with additional ball flight information (ball trajectories).…”
Section: Plos Onementioning
confidence: 99%
“…Many ball sports in VR examined interception of balls, such as anticipating landing points and analyzing the influence of ball spins. However, only a few studies investigated throwing in VR so far (for review see [37]). [40] found that learning free throws in a CAVE is best when beginners see their performance from third-person perspective and with additional ball flight information (ball trajectories).…”
Section: Plos Onementioning
confidence: 99%
“…Vestibular rehabilitation is a comprehensive, individualized exercise approach to assessing and treating symptoms due to disorders of the vestibular and balance systems. The goal of therapy is to reduce symptoms, improve postural control, gain and gaze instabilities to return to activities of daily living [10][11][12][13]18,20].…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the patient's diagnosis is a critical foundation for planning comprehensive treatment programs with the goal to reduce impairment and symptoms and expedite the return to daily activities, sports, or work [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advancement in technology and more interactive nature of the available technology, the use of applied technologies such as Virtual Reality (VR) is increasing at exponential rates in both academic and applied settings (Düking et al, 2018;Faure et al, 2020). VR is defined as simulations of a real or imaginary environment, where a participant can both perceive and interact with the environment (Craig, 2013).…”
Section: Introductionmentioning
confidence: 99%